GE_GERICHTE P/21501/2023 vom 20. Oktober 2025 - GE Cour de justice (2025)
PARTIE À LA PROCÉDURE;PLAIGNANT;LÉSÉ;DOMMAGE CAUSÉ À UN TIERS;DROIT D'ÊTRE ENTENDU;INDEMNITÉ(EN GÉNÉRAL) | CPP.382.al3; CPP.393.al2; Cst.29.al2; CPP.429